DOPPLER ULTRASONOGRAPHY OF UTERINE ARTERY IN PREGNANT CANINES - A PRELIMINARY STUDY - R, ARUN; SRIDEVI, P; JEYARAJA, K; CHANDRASEKAR, M (The Indian Journal of Animal Reproduction, 2016)
Doppler indices of uterine artery were recorded in the pregnant bitch (n=6) at different stages of gestation using doppler ultrasonography. The decrease in resistive index as gestational age advanced reflected increased perfusion towards uterus providing support for the fact that an increase in uterine blood supply is related to increased nutritional demands of growing fetus.